PLANNING AS AN EFFECTIVE TOOL FOR ENTERPRISE MANAGEMENT IN MODERN CONDITIONS - S. V. Petrov; P. A. Yurtina (Вестник университета)
The planning system as a tool for enterprise management in modern conditions has been analysed. Planning is an important function of managing any enterprise therefore success in business depends largely on the quality of planning in the organization. Without the use of a planning system, it is impossible to make the right managerial decisions, as well as to ensure their effectiveness in market conditions. In the course of the work, the relevance of the problem was identified, the publications of various authors regarding this issue were studied, different types of plans were considered. The concept and role of planning in the modern economy have been revealed, the reasons for the need for planning at the enterprise have been identified. The requirements for the planning system have been highlighted, and also the modern planning model as an effective tool for enterprise management has been presented.